Chromosomal abnormalities associated with fetal pleural effusion (II): Specific and non-specific chromosome aberrations - Chih-Ping Chen (Elsevier, 2024)
Fetal pleural effusion has been reported to be associated with chromosomal abnormalities, genetic syndromes, obstructive uropathy, lymphatic vessel abnormalities such as Noonan syndrome, RASopathy and congenital lymphatic anomalies, thoracic cavity defects, Rh or ABO incompatibility, non-immune hydrops fetalis, infections, congenital cardiac anomalies, metabolic diseases and hematologic diseases such as α-thalassemia. This review provides a comprehensive view of specific and non-specific chromosome aberrations associated with fetal pleural effusion which is useful for genetic counseling and fetal therapy at prenatal diagnosis of fetal pleural effusion.